2008
DOI: 10.1074/jbc.m703454200
|View full text |Cite
|
Sign up to set email alerts
|

A Mammalian Type I Fatty Acid Synthase Acyl Carrier Protein Domain Does Not Sequester Acyl Chains

Abstract: The synthases that produce fatty acids in mammals (FASs) are arranged as large multidomain polypeptides. The growing fatty acid chain is bound covalently during chain elongation and reduction to the acyl carrier protein (ACP) domain that is then able to access each catalytic site. In this work we report the highresolution nuclear magnetic resonance (NMR) solution structure of the isolated rat fatty acid synthase apoACP domain. Fatty acid biosynthesis in mammals is important not only for energy homeostasis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 56 publications
(64 reference statements)
5
96
0
8
Order By: Relevance
“…Although KS domains are dimeric in both Type I and Type II PKSs, in the latter the KS exists as a discrete protein without a covalently attached KS-AT linker or AT domain. This suggests that the mode of KS-ACP recognition is different in these two systems and adds to a growing body of evidence suggesting important mechanistic differences between type I and II systems (31).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although KS domains are dimeric in both Type I and Type II PKSs, in the latter the KS exists as a discrete protein without a covalently attached KS-AT linker or AT domain. This suggests that the mode of KS-ACP recognition is different in these two systems and adds to a growing body of evidence suggesting important mechanistic differences between type I and II systems (31).…”
Section: Resultsmentioning
confidence: 96%
“…In contrast the [KS3][AT3] didomain crystal structure (38) lacks the N-terminal docking domain and has an irreversible inhibitor bound at the active site of the KS domain. The apo form of the ACP was used because it has been shown that for type I systems apo-, holo-, and acyl-ACPs are conformationally similar (31,39). An additional distance constraint was applied such that the conserved serine on the ACP domain was between 12-25 Å of the active site cysteine of the KS domain to satisfy the constraint imposed by the length of the phosphopantetheine arm and search the KS surface more efficiently.…”
Section: Methodsmentioning
confidence: 99%
“…The ACP domain is located downstream of the KR domain. Based on the NMR structure of the rat FAS ACP domain and the crystal structure of the human FAS ACP domain in complex with the holo ACP synthase, ACP forms a typical four-helix bundle, with the serine for cofactor attachment preceding the second helix of the bundle (Bunkoczi et al 2007 ;Ploskon et al 2008).…”
Section: Domain Composition and Reaction Cyclementioning
confidence: 99%
“…The mechanism of acyl chain interaction with the ACP molecule is remarkably different in rat, which belongs to the type I fatty acid pathway. Insignificant interactions between the ACP molecule and the acyl chain are observed, suggesting that the ACP molecule does not sequester the acyl chain, and therefore, the acyl chain in type I pathway is protected in a way different from the type II pathway (18).…”
mentioning
confidence: 99%